Chromatin-Modifying Agents for Epigenetic Reprogramming and Endogenous Neural Stem Cell-Mediated Repair in Stroke - Qureshi, Irfan A. (2010)
The recent explosion of interest in epigenetics and chromatin biology has made a significant impact on our understanding of the pathophysiology of cerebral ischemia and led to the identification of new treatment strategies for stroke, such as those that employ histone deacetylase inhibitors. These are key advances; however, the rapid pace of discovery in chromatin biology and innovation in the development of chromatin-modifying agents implies there are emerging classes of drugs that may also have potential benefits in stroke. Herein, we discuss how various chromatin regulatory factors and their recently identified inhibitors may serve as drug targets and therapeutic agents for stroke, respectively. These factors primarily include members of the repressor element-1 silencing transcription factor (REST)/neuron-restrictive silencer factor macromolecular complex, polycomb group (PcG) proteins, and associated chromatin remodeling factors, which have been linked to the pathophysiology of cerebral ischemia. Further, we suggest that, because of the key roles played by REST, PcG proteins and other chromatin remodeling factors in neural stem and progenitor cell (NSPC) biology, chromatin-modifying agents can be utilized not only to mitigate ischemic injury directly but also potentially to promote endogenous NSPC-mediated brain repair mechanisms.